Anticipatory Coping Diversity: Implications for Emotional, Physical, and Cognitive Reactivity to Daily Stressors. (20th September 2021) - Neupert, Shevaun D
Abstract: Objectives: This study examines the concept of anticipatory coping diversity, reflected in the evenness and richness of anticipatory coping strategies. The overarching goal of this study is to show how individual differences in anticipatory coping diversity are associated with emotional, physical, and cognitive reactivity to daily stressors and to examine whether these dynamic characteristics might differ between younger and older adults. Methods: 107 younger ( M age = 19.44, range 18–36) and 116 older ( M age = 64.71, range 60–90) participants reported on 1, 627 total days via an online daily diary study. Participants reported baseline demographic information (Day 1) and anticipatory coping, stressor exposure, negative affect, physical symptoms, and memory failures (Days 2–9). Anticipatory coping diversity was indexed at the person level using Shannon's entropy to capture the evenness and richness of anticipatory coping strategies across stressors. Results: People with more anticipatory coping diversity were less emotionally reactive, but more physically and cognitively reactive to daily stressors. Older adults exhibited less anticipatory coping diversity than younger adults, but the patterns of anticipatory coping diversity differences in reactivity appeared to be consistent across younger and older adults. Discussion: Anticipatory coping diversity reflects a useful index within the stress process that is associated with benefits as well as costs. These findings bridge dispositional and contextual approaches to coping and highlight the importance of understanding how deployment of coping strategies is related to well-being across the adult life span.